PEMENUHAN SYARAT CERAI MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DALAM KASUS PENELANTARAN ISTRI YANG BERDAMPAK PADA PERCERAIAN SERTA RASA KEADILAN PENGGUGAT, STUDI KASUS PUTUSAN PENGADILAN NEGERI KUPANG NOMOR 79/PDT.G/2021PN KPG - Naisanu, Nehemia O; Aloysius, Sukardan; Mauritsius, Darius (Petitum Law Journal, 2023)
In the definition of divorce, it is said that sufficient reasons are needed for divorce, and these reasons will be proven in a court trial. Divorce cannot be done as easily as turning the palm of your hand. The most important consequence of the breakdown of a marital relationship is the division of joint assets. If a separation of assets agreement was not entered into before marriage, then the assets acquired during the marriage must be divided upon divorce. The author conducted research on the Kupang District Court Decision, Number: 79/PDT.G/2021/PN KPG, so it was deemed necessary for the author to review whether the Decision was in accordance with the problem formulation in the research on Law Number 1 of 1974 concerning Marriage. (1) Does the Kupang District Court Decision Number: 79/PDT.G/2021/PN KPG fulfill the requirements for reasons for divorce according to Law Number 1 of 1974 concerning Marriage? (2) How do the judges' considerations in the Kupang District Court Decision Number: 79/PDT.G/2021/PN KPG fulfill justice for the parties that have an impact on the divorce? This research is normative legal research with the approach method used in this research, namely: (1) Legal Approach (2) Conceptual Approach and (3) Comparative Approach then analyzed prescriptively juridically. The results of this research show that: (1) The decision given by the judge in the Kupang District Decision Number: 79/PDT.G.2021/PN KPG is clear in accordance with the reasons for the divorce in the explanation of article 39 of Law Number 1 of 1974 JO. Article 19 of Government Regulation Number 9 of 1975, states that because the plaintiff and the defendant have had separate houses and beds for up to five years, and the plaintiff has been abandoned. (2) In this case, the researcher sees that the Kupang District Court Decision Number: 79/PDT.G/2021/PN KPG, is in accordance with the actions of the plaintiff, namely that he had come to appear at the trial, but the defendant did not come to appear or asked other people to appear to appear. Represent him legally, at the trial in this case even though he had been summoned using valid court procedures, the defendant was not present at the trial and also did not show his legal representative to represent him at the trial, so that according to the researcher, there was balanced justice between the parties. those in dispute, both plaintiffs and defendants.